Variability at the 3′ untranslated region of the HLA-G gene: a study on patients with AIDS and cytomegalovirus retinochoroiditis - Vicente, Luciana de Morais; Castelli, Erick C. [UNESP]; Veronese Rodrigues, Maria de Lourdes; Deghaide, Neifi Hassan Saloum; Mendes-Junior, Celso Teixeira; Furtado, João M.; Donadi, Eduardo Antonio (Springer Nature, 2020)
Cytomegalovirus retinochoroiditis (CMV-R) is the primary cause of blindness among AIDS patients. Since HLA-G is associated with the modulation of the immune response, we hypothesized that variability at the 3′ untraslated region (3′UTR) of the gene could be implicated on the predisposition to CMV-R. We evaluated whether HLA-G 3′UTR influences CMV-R development in Brazilian AIDS patients. Peripheral blood DNA was obtained from two groups of patients: (1) AIDS exhibiting CMV-R (n = 40) and (2) AIDS without CMV-R (n = 147). HLA-G 3′UTR typing was performed using sequencing analysis. Allele, genotype and haplotype frequencies were evaluated using Fisher’s exact test accompanied by the calculation of the odds ratio and its 95% confidence interval (95% CI). The etiologic (EF) and preventive fractions were also estimated. Compared to AIDS patients without CMV-R, AIDS patients with CMV-R showed increased frequencies of the: (1) + 3001T allele, (2) the + 3001C/T genotype and (3) the UTR-17 (InsTTCCGTGACG) haplotype (EFs = 0.02–0.04). The UTR-3 (DelTCCGCGACG) haplotype was associated with protection against CMV-R development. Although the risk for developing CMR-V at the population level was relatively low (EF), the identification of HLA-G 3′UTR variation sites may help to further evaluate the role of post-transcriptional factors that may contribute to the existent immunosuppresion caused by HIV per se.